1995
DOI: 10.1021/jm00011a005
|View full text |Cite
|
Sign up to set email alerts
|

Prodrugs of Nitroxyl as Potential Aldehyde Dehydrogenase Inhibitors vis-a-vis Vascular Smooth Muscle Relaxants

Abstract: The synthesis and the chemical/biological properties of N-hydroxysaccharin (1) (2-hydroxy-1,2-benzisothiazol-3(2H)-one 1,1-dioxide), a nitroxyl prodrug, are described. When treated with 0.1 M aqueous NaOH, 1 liberated nitroxyl (HN=O), a known inhibitor of aldehyde dehydrogenase (AlDH), in a time-dependent manner. Nitroxyl was measured gas chromatographically as its dimerization/dehydration product N2O. Under these conditions, Piloty's acid (benzenesulfohydroxamic acid) also gave rise to HNO. However, whereas P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 5 publications
2
69
0
1
Order By: Relevance
“…In accordance with the mechanism proposed by Ishii and co-workers [5] the carbon radical chain promoter (NHPI or NHS) is involved in two chain propagation steps (see Scheme 5). Table 7.…”
Section: Mechanistic Considerations: Nhs Vs Nhpisupporting
confidence: 61%
See 1 more Smart Citation
“…In accordance with the mechanism proposed by Ishii and co-workers [5] the carbon radical chain promoter (NHPI or NHS) is involved in two chain propagation steps (see Scheme 5). Table 7.…”
Section: Mechanistic Considerations: Nhs Vs Nhpisupporting
confidence: 61%
“…[4] We reasoned that the use of Nhydroxysaccharin (NHS; 1b), [5] in which one carbonyl group (CO) is replaced by the more electron-withdrawing sulphonyl (SO 2 ) group, could provide an even more effective carbon radical chain promoter (CRCP). [6] In the course of our study on the oxidation of large ring cycloalkanes with molecular oxygen we found that NHS was an efficient catalyst in combination with cobalt salts.…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate that the cytotoxicity of HNO released from 1b could be amplified by its conversion to ⅐ OH in ischemia-acidified tissue (64). However, further studies are needed to understand the effects of HNO in biological systems, as well as to advance the mechanistic algorithms for interpretation and prediction of the cytotoxicity of HNO-releasing prodrugs such as Na 2 N 2 O 3 , derivatives of nitrosobenzene (10), benzisothiazol (66), chloropropamide (67), and N-hydroxybenzene carboximidate (68). …”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to expectations, extremely low concentrations of nitroxyl deactivate select thiol proteins, such as glyceraldehyde 3-phosphate dehydrogenase, without altering the cellular GSH/GSSG ratio (DeMaster et al, 1998;Paolocci et al, 2007). Pro-drugs of nitroxyl, such as derivatives of N,O-diacylated N-hydroxyarylsulfonamide (Fukuto et al, 1992) and N-acyloxy-Oarenesulfonylated benzenecarboximidic acid (Lee et al, 2001), are being developed, albeit with more emphasis on their use as vasodilators (Nagasawa et al, 1995) that are bioactivated by the esterase activity of the ALDH enzyme. In the treatment of alcohol addiction, cyanamide is a second-line drug relative to disulfiram owing to its greater capacity to induce liver injury compared with disulfiram (Tamai et al, 2000).…”
Section: G Cyanamidementioning
confidence: 99%